Analisis Keefektifan Kalimat pada Teks Esai dalam Laman “Metafor.id” Edisi April 2024 sebagai Bahan Ajar Membaca Pemahaman - Aulia Yasmin; Fathan Iqbal ‘Afi; Intan Puspita Listyani; Shinta Widiawati; Syifa Rindi Sapitri; Asep Purwo Yudi Utomo; Arum Yuliya Lestari; Ristiani Ristiani (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The effectiveness of sentences has a very important influence on the quality of the content of a literary work. In writing essays, it is important to use effective sentences so that implied and explicit messages can be conveyed clearly and well. The purpose of this study was to determine the effectiveness of sentences in essay texts on the April 2024 Edition of the "Metafor.id" Page as teaching materials for reading comprehension. This study uses two approaches, namely the methodological approach and the theoretical approach. The methodological approach uses a qualitative descriptive approach, while the theoretical approach applies syntactic analysis to evaluate the quality of content and analyze effective sentences. The data collection technique in this study uses intensive reading techniques and note-taking techniques. The data that has been collected is then analyzed using the distribution method.This research is expected to be useful for readers in writing good and correct essay texts in accordance with linguistic rules so as to produce cohesive essay texts and effectively structured sentences.